(untitled) - Bailey, Alton Edward (Hoboken, N.J., 2005)
The sixth edition of Bailey provides a comprehensive description of topics rele-vant to the oils and fats industry in six volumes as compared with five volumes in the fifth edition. The addition volume is mainly on specialty oils and fats and their by products or minor components as well as on those of low-calorie fat substitutes and structured lipid....
Keywords: Oils and fats